Influencing factors for the persistence of SARS-CoV-2 (COVID-19) exposed in environmental matrices and disinfection methods: systematic review - Yu, Chaw Chaw; Hlaing, Thein; Tun, Kyaw Myo (International Journal Of Community Medicine And Public Health, 2022)
Since the COVID-19 pandemic has been pestilential over a considerable duration, global deployment and financial crisis could not be reversed as before. It brought up essentials to allow the nations back to work with effective preventive measures. This review intended to evaluate the persistence of SARS-CoV-2 (COVID-19) exposed in the environmental matrices, influencing factors on the virus persistence and disinfection methods. Applying the PRISMA 2009 tool, MEDLINE/PubMed, HINARI, and Google Scholar were primarily explored. Data were extracted, entered into the modified data extraction forms and analysed narratively. Quality appraisal was done by the Mixed-Methods Appraisal Tool. The findings were presented descriptively. Persistence of SARS-CoV-2 was revealed <4 hours on aluminium, 4 hours on copper, 24 hours on cardboard, 44 hours on glass, 48 hours on stainless steel, 72 hours on plastic, 92 hours on polystyrene plastic, 1.1-1.2 hours in the air, 7 days (higher titer) to 3 days (lower titer) in wastewater. Virus decaying was noted 5-10 times faster at 27°C than at 10°C and 2-5 times faster with 65% relative humidity (RH) than with 40% and 100% RH. Virus infectivity was reduced by far-UVC (222 nm) light for 90% (8 minutes), 95% (11 minutes), 99% (16 minutes) and 99.99% (25 minutes). Sodium hypochlorite (800 g/m3) and ammonium-based detergents were remarkably effective for preliminary disinfection. This review identified the duration of SARS-CoV-2 survival in environmental matrices for both healthcare and non-healthcare settings. The study explored the impacts of environmental factors on the virus and effective disinfection methods to be considered accordingly to the findings.